PENGARUH PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL PADA NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CSR SEBAGAI VARIABEL PEMODERASI - Daeng Malino, Muhammad Ryan Yanuar; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
Every company is definitely trying to increase the firm value. Because by maximizing the firm value also means to maximize the prosperity of the shareholders. Investors need to gather complete and accurate information about the company to be selected as an investment venue. Investors will see some factors that can be considered as a condition of the company sucah as profitability and managerial ownership. The higher the firm’s value the better quality of the company. This study examines the effect of profitability and managerial ownership on firm value, and the existence of Corporate Social Responsibility as a moderating variable. The population of this study is a manufacturing company listed in Indonesia Stock Exchange (BEI) observation period 2013 - 2015. The number of samples of this study is 44 companies with 132 observational data. Sampling in this research using non probability method with purposive sampling technique that is by using certain criterion for sample selection. Technique of this research data analysis using Moderated Regression Analysis (MRA). Based on the results of this study found that profitability has a positive effect on the firm value. managerial ownership has been shown to negatively affect company value. Corporate Social Responsibility able to strengthen the influence of profitability on the firm value. Corporate Social Responsibility is not able to influence the relationship of managerial ownership to the firm value.